A new species of caddisfly, Leptocerus bannamradensis (Trichoptera: Leptoceridae), from Ban Nam Rad Spring, Surat Thani Province, based on morphological and molecular data - Kaewwong, Pimpajee; Kamchoo, Kanda; Tojo, Koji; Takenaka, Masaki; Malicky, Hans; Laudee, Pongsak (Zootaxa, 2026)
A new species of Leptocerus, L. bannamradensis sp. nov., is described and illustrated based on the male genitalia and molecular data. The male genitalia of L. bannamradensis sp. nov. are similar to those of L. glaukos Malicky & Chantaramongkol 2002 known from Sai Yok Waterfall, Kanchanaburi Province but differ distinctly in the inferior appendages: The basodorsal process of each inferior appendage is long and curved ventrad in L. bannamradensis sp. nov. while it is straight in L. glaukos. Additionally, fragments of mitochondrial genes, cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA), of the new species and Leptocerus dirghachuka, L. lampunensis were analysed.